Financing the Highway Function in St. Louis County: A Case Study in the Financial Practice of Government at Mid-Century - Gordman, Howard S. (Journal of Finance, 1954)
Howard S. Gordman, Financing the Highway Function in St. Louis County: A Case Study in the Financial Practice of Government at Mid-Century, The Journal of Finance, Vol. 9, No. 3 (Sep., 1954), pp. 318-319